Study of the surface oxides and corrosion behaviour of an equiatomic CoCrFeMnNi high entropy alloy by XPS and ToF-SIMS. (1st May 2020) - Wang, Luntao; Mercier, Dimitri; Zanna, Sandrine; Seyeux, Antoine; Laurent-Brocq, Mathilde; Perrière, Loïc; Guillot, Ivan; Marcus, Philippe
Highlights: Surface oxide layers formed on CoCrFeMnNi High Entropy Alloy are investigated by XPS and ToF-SIMS. An XPS methodology based on analysis of the 3p core level spectra was developed. The native oxide and passive films are compared. The oxide film on HEA is duplex comprising a Cr/Mn inner oxide layer and a Cr/Fe/Co outer oxide/hydroxide layer. The effect of electrochemical passivation on the surface oxide layer is discussed. Abstract: XPS and ToF-SIMS analysis have been combined with electrochemical measurements to determine the corrosion behavior of the equiatomic CoCrFeMnNi high entropy alloy. An XPS methodology based on analysis of the 3p core level spectra was developed to determine the composition and thickness of oxide films. Both native oxide (∼1.4 nm) and passive films (∼ 1.6 nm) formed in acidic medium are duplex, comprising Cr and Mn inner layer and Cr/Fe/Co mixture outer layer. No nickel is observed in the oxide layer. The effects of exposure of the native film to sulfuric acid and passivation under anodic polarization have been investigated.